Natural products as new photoprotection strategies - Godoy, Mauren Knorst; Nunes, Viviane Cecília Kessler; Bonfanti-Azzolin, Gabriela (Revista de Ciências Médicas e Biológicas, 2024)
Objective: to investigate the photoprotective efficacy of natural products in in vivo models. Methodology: this is an integrative literature review based on articles published between 2015 and 2020 in English, found on electronic platforms with the following keywords: natural sunscreens, medicinal plants, ultraviolet radiation (UVR), ultraviolet rays, sunscreens, and plant extracts. Results: 96 articles were identified on the electronic platforms Pubmed, Science Direct, Scielo, and Springer, and eight articles were selected for final analysis and discussion. The compiled data showed that experimental animal models stood out from human models. As for UVR-induced damage, the general effects presented by natural products are radiation absorption, erythema, hyperplasia, and induced carcinogenesis reduction; anti-inflammatory and antioxidant effects; and reduction of signs of photoaging, such as wrinkles, rashes, and skin dehydration. Regarding the type of radiation used, UVB studies are prevalent, but some extracts demonstrate protective effects against UVA and UVB, presenting a broad spectrum of protection. Regarding the form of administration, the findings emphasised the topical route, with formulations with plant extracts being the most used. Conclusion: despite the low number, in vivo, studies prove that using natural products such as sunscreens has benefits in inhibiting, delaying, or preventing oxidative, inflammatory, carcinogenic damage and aesthetic dysfunctions caused by UV radiation. Thus presenting the potential to be used as a multifunctional sun protection system.